Sosialisasi Model Pengembangan Kurikulum Bahasa Inggris Berbasis Kearifan Lokal di SMK - Dedi Aprianto; Lalu Zazuli Azhar Mardedi; Haryono; Sasih Gunalan; I Nyoman Miyarta Yasa (Insan Kreasi Media, 2023)
This community service program was aimed at socializing on how local wisdom-based English curriculum development model carried out for the Public Vocational High School English teachers. Curriculum design by integrating local cultural elements into the development of English language teaching materials is an important uniqueness in the development of the vocational students’ local cultural competencies and linguistics aspects. The method of implementing the community service was carried out by providing socialization of the curriculum development model which is carried out using the lecturing model and Focused Group Discussion (FGD). The results suggest the socialization of local wisdom-based English curriculum development activities is positive with a score scale of 3.01-4.0. There are two important elements in curriculum development by considering the students’ needs, namely elements of local cultural knowledge and linguistic knowledge. There are three requirements in a curriculum development, namely noticing at the students' needs & necessity, learning needs and the patterns of a curriculum design on how to structurally develop.